1986
DOI: 10.1288/00005537-198603000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the tonsillar region

Abstract: A retrospective analysis of 171 patients with carcinoma of the tonsillar region is presented. The majority of patients (79%) presented with stage III and IV disease. Three year determinate survival was 81% - T1, 74% - T2, 59% - T3, and 20% - T4. The presence of nodal disease decreased survival by one half. Radiotherapy alone was highly successful in controlling early T1 and T2 lesions of the tonsillar fossa. Surgery alone or combined radiotherapy and surgery was more successful than radiotherapy in controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Similar results have been described by Fayos and Lampe: Mantravadi et a1., 22 Nussbaum et al, 23 Wang,' and Mizono et a1. 24 Million and Cassisi: Mendenhall et a1.,l6 Perez et al, 25 and Shukovsky and Fletcherlg have indicated that doses of 6,000 to 6,500 cGy are adequate to control T1 lesions and 7,000 cGy is s a c i e n t for most T2 tumors delivered with 180 to 200 cGy per day in 5 weekly fractions. However, biologic doses significantly greater than 7,000 cGy are necessgry to achieve satisfactory tumor control in T3-T4 tumors or N3 cervical lymph nodes.…”
Section: Carcinoma Of the Tonsil Has Been Primarily Treated With Irramentioning
confidence: 99%
“…Similar results have been described by Fayos and Lampe: Mantravadi et a1., 22 Nussbaum et al, 23 Wang,' and Mizono et a1. 24 Million and Cassisi: Mendenhall et a1.,l6 Perez et al, 25 and Shukovsky and Fletcherlg have indicated that doses of 6,000 to 6,500 cGy are adequate to control T1 lesions and 7,000 cGy is s a c i e n t for most T2 tumors delivered with 180 to 200 cGy per day in 5 weekly fractions. However, biologic doses significantly greater than 7,000 cGy are necessgry to achieve satisfactory tumor control in T3-T4 tumors or N3 cervical lymph nodes.…”
Section: Carcinoma Of the Tonsil Has Been Primarily Treated With Irramentioning
confidence: 99%
“…Oropharyngeal cancer is a common head and neck cancer and, in particular, tonsillar cancer has increased recently. More than half of the patients with tonsillar cancer present with typically lymphatic metastasis (stage III or IV) and the prognosis is commonly predicted using the T classification (tumor size) and N classification (lymph node status) . To our knowledge, no report in the English‐language literature has assessed the prognostic significance of lymph node density in predicting the risks of disease recurrence and survival in patients with oropharyngeal cancer, especially in patients with tonsillar cancer separately.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the patients with tonsillar cancer present with typically lymphatic metastasis (stage III or IV) and the prognosis is commonly predicted using the T classification (tumor size) and N classification (lymph node status). 15,16 To our knowledge, no report in the English-language literature has assessed the prognostic significance of lymph node density in predicting the risks of disease recurrence and survival in patients with oropharyngeal cancer, especially in patients with tonsillar cancer separately. We designed this study to assess the value of lymph node density in predicting survival after surgery for patients with tonsillar cancer and positive neck nodes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] There are no dedicated randomized trials that have focused on comparing radiotherapy versus surgery for oropharyngeal carcinoma. Radiotherapy is preferred at many centers because of presumed lower morbidity and better functional and cosmetic outcome compared with surgical treatment, particularly with the increased use of chemoradiation.…”
mentioning
confidence: 99%